ICT tools for listening and speaking skills in English teaching and learning: Advantages and challenges in digital globalization era - Nathania, Stella (Journal of Environment and Management, 2024)
ICT as a common tool has been used for all the aspect of life and its impact to support the English teaching and learning especially for listening and speaking skills. The recent study aims to explore the kinds of ICT tools for listening and speaking skills in English teaching and learning and also to investigate the advantages and challenges of using those tools in digital globalization era. The method of this study is literature review with narrative review approach. This study focused on integrating different kinds of ICT tools to enhance listening as well as speaking skill and the advantages and challenges in using it. The types of ICT are divided into 2 which are non-web-based learning included (1) movie/film, (2) radio and television, (3) LCD projector, and (4) language lab and web-based learning included (1) website, (2) application, and (3) You-Tube. Then, present information and explanation the advantages and challenges of those ICT tools in digital globalization era. The result of this study is expected to be beneficial as references for educators in understanding the kinds of ICT tools for listening and speaking skills and also the advantages and challenges in using it for English teaching and learning in digital globalization era.